Social media facilitates disclosure among people experiencing child maltreatment: A brief report - Laura M. Schwab-Reese; Morgan E. PettyJohn; Rafia Tasnim; Michelle Fingerman (Child Protection and Practice)
Background: Many victims, particularly adolescents, must disclose abuse or neglect to have their experiences identified by people able to provide support and resources. Social media may be part of how young people seek support. Objective: This brief reports the percentage of young victims of maltreatment who use social media to disclose their experiences and describes the most used platforms. Participants, setting, and methods: Of the 641 individuals who completed a screening survey via Connect on CloudResearch, 111 experienced childhood maltreatment and shared their experiences on social media. Of these, 26 participants completed a follow-up survey. Findings: Almost all respondents in the follow-up survey reported offline disclosure (n = 24; 92 %), although telling an adult offline was less common (n = 19; 73 %). Most participants disclosed maltreatment on multiple platforms (n = 22; 85 %), usually on two or three platforms (n = 14; 54 %). Although it was common to use anonymous accounts to talk about maltreatment, 80 % of participants posted at least once on their personal accounts. Conclusion: This study identifies the importance of social media for young people's maltreatment disclosures. Social media platforms and users need to be prepared to respond appropriately.